Clinical ethics committees in nursing homes: what good can they do? Analysis of a single case consultation - Magelssen, Morten (Nursing ethics, 2022)
Background:Ought nursing homes to establish clinical ethics committees (CECs)? An answer to this question must begin with an understanding of how a clinical ethics committee might be beneficial in a nursing home context – to patients, next of kin, professionals, managers, and the institution. With the present article, we aim to contribute to such an understanding.Aim:We ask, in which ways can clinical ethics committees be helpful to stakeholders in a nursing home context? We describe in depth a clinical ethics committee case consultation deemed successful by stakeholders, then reflect on how it was helpful.Research design:Case study using the clinical ethics committee’s written case report and self-evaluation form, and two research interviews, as data.Participants and research context:The nursing home’s ward manager and the patient’s son participated in research interviews.Ethical considerations:Data were collected as part of an implementation study. Clinical ethics committee members and interviewed stakeholders consented to study participation, and also gave specific approval for the publication of the present article.Findings/results:Six different roles played by the clinical ethics committee in the case consultation are described: analyst, advisor, support, moderator, builder of consensus and trust, and disseminator.Discussion:The case study indicates that clinical ethics committees might sometimes be of help to stakeholders in moral challenges in nursing homes.Conclusions:Demanding moral challenges arise in the nursing home setting. More research is needed to examine whether clinical ethics committees might be suitable as ethics support structures in nursing homes and community care.